TRENDS AND CHALLENGES IN PHYTOTHERAPY AND PHYTOCOSMETICS FOR SKIN AGING - Idris Adewale, Ahmed; Maryam Abimbola, Mikail; Nor Hisam, Zamakshshari; Mohd Rais, Mustafa; Najihah, Mohd Hashim; Rozana, Othman (Elsevier B.V, 2022)
Oxidative stress and inflammation mostly contribute to aging and age-related conditions including skin aging. The potential of natural products in the form of naturally-derived cosmetics, cosmeceuticals, and nutricosmetics have, however, not been fully harnessed. This review, thus, critically analyzes the potential roles of natural products in inflammation-related skin aging diseases due to the increasing consumers’ concerns and demands for efficacious, safe, natural, sustainable, and religiously permitted alternatives to synthetic products. The information and data were collated from various resources and literature databases such as PubMed, Science Direct, Wiley, Springer, Taylor and Francis, Scopus, Inflibnet, Google, and Google Scholar using relevant keywords and Medical Subject Headings (MeSH). The role of green extraction solvents as promising alternatives is also elucidated. The potential enhancements of the bioavailability, stability, solubility and controlled release profile of the bioactives using different delivery systems are also presented. The current potential global market value, motivators, drivers, trends, challenges, halal, and other regulatory certifications for cosmeceuticals and nutricosmetics are equally discussed. The adoption of the suggested extractions and delivery systems would enhance the stability, bioavailability, and target delivery of the bioactives.